2006
DOI: 10.1203/01.pdr.0000246071.50268.51
|View full text |Cite
|
Sign up to set email alerts
|

Altered Postnatal Lung Development in C3H/HeJ Mice

Abstract: C3H/HeJ mice develop an increase in terminal air space area detectable by postnatal d 14 that persists into adulthood compared with strain-matched controls (C3H/SnJ, C3H/OuJ). Morphometric quantification revealed a 50% increase in terminal air space area by postnatal d 14 and a 2.3-fold increase by 2 mo of age in C3H/HeJ mice. Bacteriologic cultures obtained from the left lung on postnatal d 7 revealed Ͼ100 colony-forming units (CFU)/left lung of predominantly Gram-negative bacteria (GNB) (Escherichia coli and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…The expression and secretion of ECM-modifying MMPs is an important determinant of tumor invasion. MMP expression is regulated at the transcriptional level and the MMP promoters contain NF-kB (Chen et al, 2009;Oh et al, 2009), which have been shown to regulate MMP-12 promoter activity (Castrillo et al, 2003;Sampath et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The expression and secretion of ECM-modifying MMPs is an important determinant of tumor invasion. MMP expression is regulated at the transcriptional level and the MMP promoters contain NF-kB (Chen et al, 2009;Oh et al, 2009), which have been shown to regulate MMP-12 promoter activity (Castrillo et al, 2003;Sampath et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Cells were plated in 24-well dishes at 30% confluency and transfected on the following day in DMEM supplemented with 0.2% serum without antibiotics. HEK-293 cells do not express any of the TLR family members and are used to monitor regulation of TLR activity introduced by transient cell transfection (29). Plasmids were prepared using endotoxin-free kits (Qiagen).…”
Section: Detection Of Sp-a and Sp-d By Western Blotmentioning
confidence: 99%
“…Infection of the lung with Klebsiella pneumoniae (KPA1 serotype, cps K2) was via intratracheal delivery (33,34). Lung bacterial burden was quantified by plating serial dilutions of lung homogenates (34,35) onto blood agar plates. BALF cell counts and differential were performed as described (35).…”
Section: Methodsmentioning
confidence: 99%